Graffiti Bentuk Ekspresi Berbahasa Masyarakat Kota Singkawang - NFN Martina (Balai Bahasa Kalimantan Barat, 2017)
This research raised graffiti the form of expression the public speaking singkawang. The purpose of this research is described graffiti the form of expression the public speaking singkawang. Methods used is the method descriptive with a qualitative approach. The analysis showed that the work of graffiti a form of expression-speaking community Singkawang classified into 4 parts, the graffiti that expresses a sense of nationalism, the expression of an appeal (the teachings of Confucianism, the teachings of Islam, and the appeal of health in the form of family planning), the expression of the ad/promo, and self-expression.